(untitled) (Universal International Scientific Journal, 2026)
In this work, the synthesis of nanocontainers based on quercetin, a representative of the flavonoid class, and molybdenum(II) cations was investigated. The synthesis process was carried out in a solution medium under alkaline conditions, resulting in the formation of coordination nanostructures via a self-assembly mechanism. The obtained nanocontainers are characterized by high stability and functional properties and are considered promising for applications in catalysis and other applied fields